An investigation of principals' perceptions and experiences of the implementation of the national standards and performance indicators (NSPI) for Namibian schools in the Ohangwena region - Johannes, Thomas Kamusheefa (Rhodes University, Faculty of Education, Department of Education, 2010)
The post independence Namibian education system has been characterised by many reform initiatives, aimed at eradicating inequity, poor performance, and inferior education provision inherited from a pre-independence education system. This legacy posed a serious challenge to Namibia when it set out to achieve a national goal, Vision 2030. Vision 2030 inspires Namibia to be among the eveloped countries in 2030. In an attempt to achieve the goals outlined by the mission statement of Vision 2030, the Ministry of Education (MoE) introduced two national education initiatives: the Education and Training Sector Improvement Program (ETSIP), and the National Standards and Performance Indicators (NSPIs). These would be implemented in Namibian schools as, respectively, the Ministry's strategic plan and its policy document. The NSPIs were introduced to address the fragmentation of standards and inequity in regions and schools in Namibia, as they aimed to standardise the provision of equal, quality education across the country (Namibia. MoE, 2005a, p. 1). The NSPI policy calls for schools to take quality assurance seriously, with particular emphasis on School Self-Evaluation (SSE), a process that encourages self-management (Namibia. MoE, 2007a, p. 3). Thus, the standards set out by the NSPIs became the yardstick by which internal and external school evaluators could assess whole school performance. The purpose of this present study was to investigate the perceptions and experiences of principals in the Ohangwena Region following the implementation of the NSPIs. It is a case study involving two Inspectors of Education (IoEs), twelve principals, and four Heads of Department (HODs). Interviews, document analysis, questionnaires, and a focus group interview were used to collect the data. The study found that principals acknowledge the importance of the NSPIs, and believe that they would succeed in improving the provision of quality education if they were fully implemented. The study found that schools implemented Performance Indicators 5.3 (School Administration) Aspect 5.3.2 (Storage and retrieval of information) in Key Area 5. However, the results of the study also showed that principals experienced many challenges in the implementation of the NSPIs. These included a lack of understanding among principals and teachers of the NSPIs, a lack of understanding of contemporary leadership theories (that would otherwise help principals to implement change effectively), and a lack of support in terms of skills and resources from both the Regional Office in Ohangwena and the MoE itself. The study found that the NSPIs have not yet improved school performance, and consequently that the pass rate remains the same as before the introduction of the NSPIs, four years ago. The SSE, which aims to help schools identify their strengths and weaknesses, and encourages them to establish and make use of a School Development Plan (SDP) to address weaknesses and sustain strengths, is characterised by a high degree of dishonesty. Thus, the information furnished by SSEs, SDPs, and Teachers Self-Evaluations (TSEs) is unreliable, lacks credibility, and has the further ill-effect of skewing schools' performance targets. Therefore, this problem could be addressed when the rationale of completing the SSE is clearly explained to principals and teachers.
Keywords: Professional education -- Namibia; Educational change -- Namibia; Education -- Namibia; Education and state -- Namibia; School management and organization -- Namibia